(untitled) (Archaeologia Adriatica, 2012)
In a detailed analysis and critical examination of currently known facts about the fragments of a pre-Romanesque altar rail found at the Begovača site in Biljane Donje near Zadar, the author uncovers important facts. These are not only linked to the fragments and their epigraphic context, but are also significant in determining the onstruction development stages of the site, as already discussed in Croatian archaeology and art history circles. New evidence confirms the assumption that there was a larger early Christian church on the site which was rebuilt and furnished with new liturgical fittings in the Early Middle Ages, and replaced by a significantly smaller Romanesque church in the course of the high Middle Ages. A combination of recognising the construction features of the preserved fragments and their artistic-morphological and epigraphic characteristics, also confirms the attribution of the aforementioned fragment to a Stonemasonry workshop from the period of Prince Trpimir, since on part of the votive inscription of one of the fragments of the architrave, the name of the Croatian Prince Mislav can be identified. he was the immediate predecessor of Trpimir, which thus dates the reconstruction of the early Christian church more firmly to the period of Mislav’s reign, i.e. the fourth decade of the 9th century, while the production of the stonemasonry can be dated to approximately the second quarter of the same century.